Hexakis(dimethyl sulfoxide-kappa O)cobalt(III) trinitrate - Li, Q.; Ng, S.W. (International Union of Crystallography, 2010)
The metal atom of the title salt, [Co(C(2)H(6)OS)(6)](NO(3))(3), is coordinated by six dimethyl sulfoxide molecules in an octahedral geometry. The metal atom lies on a special position of (3) over bar site symmetry. One of the nitrate ions lies on a special position of 3 site symmetry and the other independent ion is disordered about a special position of (3) over bar site symmetry